2020
DOI: 10.35848/1882-0786/ab8054
|View full text |Cite
|
Sign up to set email alerts
|

Tunable circular dichroism of stretchable chiral metamaterial

Abstract: Circular dichroism (CD) of a stretchable chiral metamaterial with bilayer L-shaped and T-shaped Au patterns on the Polydimethylsiloxane substrate (SCMM-BLT) is investigated theoretically. Due to the excitation of plasmonic hybridization modes, CD effect happens. SCMM-BLT can produce large optical chirality (OC) of 53.6% in mid-infrared region, and we attribute the double bands of CD to the excitation of the bonding and antibonding modes. By stretching SCMM-BLT, the bands of CD shift to longer wavelengths, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In contrast to [22], the proposed unit cell with a metal pattern on only one side of the printed circuit board (PCB) is intrinsically achiral. Through numerical and experimental characterization, we show that these nonplanar structures can present large CD values, up to 0.9, which are higher than those presented by conventional intrinsic CMMs, around 0.6 [27], [28], [29], but also by the planar distribution with oblique incidence. This improvement in the CD resides in the interaction between the unit cells, that is, mutual coupling.…”
mentioning
confidence: 88%
“…In contrast to [22], the proposed unit cell with a metal pattern on only one side of the printed circuit board (PCB) is intrinsically achiral. Through numerical and experimental characterization, we show that these nonplanar structures can present large CD values, up to 0.9, which are higher than those presented by conventional intrinsic CMMs, around 0.6 [27], [28], [29], but also by the planar distribution with oblique incidence. This improvement in the CD resides in the interaction between the unit cells, that is, mutual coupling.…”
mentioning
confidence: 88%
“…However, all these devices typically lack tuning ability because the chiral eigenstates are often determined by structural parameters such as period and height, and optical functions become fixed once the fabrication is completed. Many efforts have been made to achieve dynamic control of CD behavior in which active materials with externally applied electro-voltage, optical fields, temperature, forces or even chemical reactions are employed, such as applying an external voltage to graphene, , liquid crystals, and other meta-atoms, , injecting extra photons to achieve chiral switch based on physical properties and chemical reactions , of materials, adjusting the temperature to trigger the phase transition of the materials or assembling or applying external forces , on a flexible material substrate (like polydimethylsiloxane and hydrogel). However, the performance of these actively tuned devices is often limited to weak chirality and poor regulation ability due to the limited performance of the available active materials.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metamaterials or metasurfaces have attracted increasing attention. [7,8] Researchers have found that they can easily modulate the polarization modes of electromagnetic (EM) waves. [9][10][11][12][13] To date, a series of novel polarization converters have been realized and studied by using metasurface, [14][15][16][17][18][19][20] which greatly promote the development of optoelectronics and optical communication.…”
Section: Introductionmentioning
confidence: 99%